Thermal performance improvement for residential buildings in the tropics through the application of green façade and green roof - Abass Younis, Fatma Hussien (2021)
Green envelope strategies are a passive cooling technique adopted to lessen surfaces temperature due to the heat capacity storage of vegetation lower than the other structure materials. This research assesses the green façades and green roofs to rate heat transfer through building envelopes and cooling load. The research used the Overall Thermal Transfer Value (OTTV) index to calculate the thermal performance of selected case studies and developed computational workflows. Moreover, the Green Building Studio simulated the annual energy consumption through bare and vegetated envelopes scenarios. Three tropical species climbers, Hedera Helix, AntigononLeptopus, and Lonicera Japonica, were chosen to assess the thermal impact of a green façade applied to a bare opaque wall. In comparison, the green roof's lawn was limited to a single variety (Cow grass). The results indicated that the Hedera Helix climber's thermal performance was superior to the other climbers. The implementation of green façade and green roof reduced OTTV and steady-state heat gain of roofs of case study buildings by 19 % and 90%, respectively. Thus, the overall annual and monthly energy consumption reduction achieved by 11% and 14%, respectively; in parallel, the annual carbon dioxide (CO2) emissions from energy consumption dropped to 13%. On the other hand, the correlation between the annual cooling loads and corresponding OTTV for residential buildings revealed a strong relationship between the annual cooling load and the OTTV amount. Regarding the validation of the developed OTTV computational workflow, it was found that tolerance between the proposed systems and the manual calculation is approximately 0% to 2.17 % within the acceptable range. In conclusion, green facades and roofs help reduce the U-value of the building’s envelope, reduce heat transfer and lower cooling loads, carbon dioxide (CO2), and electricity costs. A simple and flexible approach to calculating the total heat transfer value (OTTV) and the proposed U-value with little human error and immediate results when determining the average heat transfer into a building.